Teks Berita Pemilu 2024 Dalam Media Instagram Tempo.co Dimensi Discourse Practice: Kajian AWK Norman Fairclough - Juliana, Hera; Juanda, Juanda; Saguni, Suarni Syam; Afandi, Iswan (Fakultas Teknik Universitas Negeri Makassar, 2025)
This study aims to analyze news texts about the 2024 Election published by the Tempo.co Instagram account through Norman Fairclough's critical discourse analysis approach. The research method used is descriptive qualitative, focusing on experiential, relational, and expressive value in the text displayed. Data were collected through reading and note-taking techniques, and the validity of the data was tested through triangulation. The study results show that experiential value is evident from frequently repeated ideological vocabulary, metaphors, and lexical terms that convey complex meanings. Relational value is seen through formal and informal words, which indicate the social relationship between political actors and the audience. Meanwhile, expressive value is reflected in the positive and negative evaluations used in the text, describing the social and political identity of the figures reported. Through the process of text production and consumption, news on Tempo.co Instagram is interpreted differently by the audience, allowing for the formation of various perspectives in understanding current political issues. This study shows how election discourse on social media can create critical interpretations in society and shape public opinion.